Electrode plate complex, preparation method of electrode plate complex, all-solid-state battery and application of all-solid-state battery

By preparing the interface layer between the polyanionic layer and the polycationic layer in an all-solid-state battery, and debonding it by IDL voltage regulation, the problem of cracking of the sulfide solid electrolyte layer during the transfer process is solved, achieving efficient and complete Improved transfer and battery performance.

CN119481331APending Publication Date: 2025-02-18ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411631717.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In all-solid state batteries, the sulfide solid electrolyte layer is prone to cracking during the transfer process, resulting in low mechanical strength of the layer, affecting the overall performance and reliability of the battery.

Method used

The interface layer and the solid electrolyte layer are prepared in turn on the surface of the conductive substrate. The interface layer consists of a polyanionic layer and a polycationic layer. It is debonded by regulating the IDL voltage, and the solid electrolyte layer and polycationic layer are transferred to the electrode sheet. on the active material coating.

Benefits of technology

The transfer efficiency and integrity of the solid electrolyte layer are improved, the overall performance and reliability of the battery are enhanced, and the side reaction between the solid electrolyte layer and the electrode sheet is improved through the polycation layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481331A_ABST
    Figure CN119481331A_ABST
Patent Text Reader

Abstract

The invention relates to an electrode plate complex and a preparation method thereof, an all-solid-state battery and application thereof, and the preparation method of the electrode plate complex comprises the following steps: sequentially preparing an interface layer and a solid electrolyte layer on any surface of a conductive substrate to obtain a transfer printing part, the interface layer comprises a polyanion layer and a polycation layer which are sequentially stacked on the conductive base material; providing an electrode plate, attaching the electrode plate to a transfer printing part, enabling the solid electrolyte layer of the transfer printing part to be in contact with the active material coating of the electrode plate, then applying voltage between the transfer printing part and the electrode plate, and enabling the solid electrolyte layer and the polycation layer in the transfer printing part to be transferred to the surface of the active material coating of the electrode plate, and obtaining the electrode plate complex. By adopting the preparation method disclosed by the invention, the solid electrolyte layer can be completely transferred to the electrode plate, and when the electrode plate complex is applied to the all-solid-state battery, the overall performance and reliability of the all-solid-state battery can be ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to an electrode sheet composite and a preparation method thereof, an all-solid-state battery and applications thereof. Background Art

[0002] In traditional liquid batteries, polar solvents and binders with polar groups are usually used. These polar materials can effectively provide the required bonding strength to meet the processing and use requirements of lithium-ion batteries. However, in all-solid-state batteries, the chemical stability of sulfide solid electrolytes in polar materials is poor and they are prone to reaction. Therefore, non-polar or weakly polar materials must be selected as alternatives. However, the interaction between non-polar or weakly polar materials and sulfide solid electrolytes is weak, resulting in low mechanical strength of the sulfide solid electrolyte layer, which leads to cracking of the sulfide solid electrolyte layer during the transfer process, making it impossible to completely transfer the sulfide solid electrolyte layer to the positive and negative electrodes, affecting the overall performance and reliability of the all-solid-state battery. Summary of the invention

[0003] Based on this, it is necessary to provide an electrode sheet complex and its preparation method, an all-solid-state battery and its application to address the above problems. The preparation method can completely transfer the solid electrolyte layer to the electrode sheet to ensure the overall performance and reliability of the all-solid-state battery.

[0004] A method for preparing an electrode sheet composite comprises the following steps:

[0005] An interface layer and a solid electrolyte layer are sequentially prepared on any surface of a conductive substrate to obtain a transfer component, wherein the interface layer comprises a polyanion layer and a polycation layer sequentially stacked on the conductive substrate;

[0006] An electrode sheet is provided, and the electrode sheet is laminated to the transfer component so that the solid electrolyte layer of the transfer component contacts the active material coating of the electrode sheet. Then, a voltage is applied between the transfer component and the electrode sheet so that the solid electrolyte layer and the polycationic layer in the transfer component are transferred to the surface of the active material coating of the electrode sheet, thereby obtaining an electrode sheet complex.

[0007] In one embodiment, the anionic polymer used in the polyanionic layer is at least one selected from a copolymer of 3-sulfopropyl acrylate lithium and 1-ethyl-3-methylimidazolium chloride, and a copolymer of polystyrene benzyltrimethylammonium chloride and hydrogenated polybutadiene;

[0008] And / or, the cationic polymer used in the polycationic layer is at least one selected from a copolymer of 2-bromoethyl acrylate and 1-butylimidazolium, and 1-(6-(acryloyloxy)-hexyl)-3-ethylimidazolium-bis(trifluoromethylsulfonyl)imide.

[0009] In one embodiment, the polycation layer further includes a lithium salt.

[0010] In one embodiment, the thickness of the polyanion layer and the polycation layer are independently selected from 0.1 μm-10 μm.

[0011] In one of the embodiments, when a voltage is applied between the transfer component and the electrode sheet, the voltage intensity is 0.1V-5V, and the current direction is from the transfer component to the electrode sheet.

[0012] In one embodiment, the solid electrolyte layer is selected from a sulfide solid electrolyte layer;

[0013] And / or, the thickness of the solid electrolyte layer is 10 μm-100 μm.

[0014] In one embodiment, the electrode sheet is selected from a positive electrode sheet or a negative electrode sheet.

[0015] An electrode sheet complex is prepared by the method for preparing the electrode sheet complex, comprising an electrode sheet and a solid electrolyte layer and a polycation layer which are sequentially stacked on an active material coating of the electrode sheet.

[0016] An all-solid-state battery comprises the electrode sheet composite.

[0017] An electrical device using the all-solid-state battery.

[0018] In the present invention, an interface layer composed of a polyanion layer and a polycation layer is added between the solid electrolyte layer and the conductive substrate. In the interface layer, the polyanion layer and the polycation layer with opposite charges can form an ionic double layer (IDL) at the interface, which is similar to the space charge layer formed at the p / n junction of an electronic semiconductor. Therefore, the polyanion layer and the polycation layer can be debonded by regulating the IDL voltage, and the solid electrolyte layer and the polycation layer are transferred to the active material coating of the electrode sheet together, thereby ensuring the transfer efficiency and integrity of the solid electrolyte layer. In addition, the polycation layer has ion conduction ability, which not only does not affect the performance of the all-solid-state battery, but also can serve as an interface to improve the side reactions between the solid electrolyte layer and the electrode sheet, thereby ensuring the overall performance and reliability of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the conventional technology, the drawings required for use in the embodiments or the conventional technology descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 It is a schematic structural diagram of the transfer component of the present invention;

[0021] Figure 2 It is a schematic diagram of the transfer process in the preparation process of the electrode sheet composite of the present invention.

[0022] In the figure: 1, transfer component; 2, electrode sheet; 11, conductive substrate; 12, interface layer; 13, solid electrolyte layer; 121, polyanion layer; 122, polycation layer. DETAILED DESCRIPTION

[0023] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0025] In the present invention, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0026] Combination Figure 1 and Figure 2As shown, the method for preparing the electrode sheet composite provided by the present invention comprises the following steps:

[0027] An interface layer 12 and a solid electrolyte layer 13 are sequentially prepared on any surface of a conductive substrate 11 to obtain a transfer component 1, wherein the interface layer 12 includes a polyanion layer 121 and a polycation layer 122 sequentially stacked on the conductive substrate 11;

[0028] Provide an electrode sheet 2, and fit the electrode sheet 2 to the transfer component 1 so that the solid electrolyte layer 13 of the transfer component 1 contacts the active material coating of the electrode sheet 2, and then apply a voltage between the transfer component 1 and the electrode sheet 2 so that the solid electrolyte layer 13 and the polycation layer 122 in the transfer component 1 are transferred to the surface of the active material coating of the electrode sheet 2, thereby obtaining an electrode sheet complex.

[0029] The polyanion layer 121 and the polycation layer 122 carry opposite charges. In the preparation method of the present invention, an interface layer 12 composed of the polyanion layer 121 and the polycation layer 122 is added between the solid electrolyte layer 13 and the conductive substrate 11. In the interface layer 12, the polyanion layer 121 and the polycation layer 122 can form an ionic double layer (IDL) at the interface, which is similar to the space charge layer formed at the p / n junction of an electronic semiconductor. Therefore, by regulating the IDL voltage, the polyanion layer 121 and the polycation layer 122 can be debonded, and the solid electrolyte layer 13 and the polycation layer 122 can be transferred to the active material coating of the electrode sheet 2 together, thereby ensuring the transfer efficiency and integrity of the solid electrolyte layer 13. In addition, the polycation layer 122 has ion conductivity, which not only does not affect the performance of the all-solid-state battery, but also can serve as an interface to improve the side reactions between the solid electrolyte layer 13 and the electrode sheet 2, thereby ensuring the overall performance and reliability of the all-solid-state battery.

[0030] It can be understood that the present invention has no special requirements for the selection of the conductive substrate 11. Conductive flexible substrates such as copper foil, aluminum foil, carbon-coated copper foil, carbon-coated aluminum foil, and conductive rigid substrates can be used.

[0031] Similarly, the present invention does not make special requirements for the anionic polymer used in the polyanionic layer 121 and the cationic polymer used in the polycationic layer 122 in the interface layer 12. Conventional anionic polymers and cationic polymers can construct the interface layer 12 and form an ionic double layer (IDL). Preferably, the anionic polymer is selected from at least one of a copolymer of 3-sulfopropyl acrylate lithium and 1-ethyl-3-methylimidazolium chloride, and a copolymer of polystyrene benzyltrimethylammonium chloride and hydrogenated polybutadiene; the cationic polymer is selected from at least one of a copolymer of 2-bromoethyl acrylate and 1-butylimidazolium, and 1-(6-(acryloyloxy)-hexyl)-3-ethylimidazolium-bis(trifluoromethylsulfonyl)imide.

[0032] It is understandable that when preparing the polyanion layer 121 and the polycation layer 122, a crosslinking agent and an initiator are also required. Specifically, an anionic polymer, a crosslinking agent and an initiator can be mixed and reacted and then coated on the conductive substrate 11 to form the polyanion layer 121, and a cationic polymer, a crosslinking agent and an initiator can be mixed and reacted and then coated on the polyanion layer 121 to form the polycation layer 122.

[0033] Among them, the crosslinking agent can be selected from at least one of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetraacrylate, pentaerythritol triacrylate, ethoxylated trimethylolpropane triacrylate, methyl formate and polyether acrylate, and the initiator can be selected from azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide, stannous octoate, lithium acetate, At least one of triethyl phosphine, triphenyl phosphine, tri-n-butyl phosphine, tributyl tin oxide, tetrabutyl titanate, tetrabutyl zirconate, trialkyl tin alkoxide, dialkyl tin oxide, N-methylethylenediamine, dimethylformamide, triethyleneethylenediamine, methyldiethylene glycolamine, triethylenediamine, aluminum trifluoromethanesulfonate, magnesium trifluoromethanesulfonate, lithium bis(fluorosulfonyl)imide and tin trifluoromethanesulfonate. The specific selection and dosage can be matched according to the anionic polymer and the cationic polymer, and the present invention will not elaborate on it.

[0034] Since the polycation layer 122 will be transferred to the active material coating of the electrode sheet 2 together with the solid electrolyte layer 13, lithium salts such as LiTFSI, LiFSI, etc. can be further added when preparing the polycation layer 122. At this time, the polycation layer 122 also includes lithium salts, which can further improve the ionic conductivity of the polycation layer 122. The amount of lithium salt added to the polycation layer 122 is not limited. Preferably, the mass fraction of the lithium salt in the polycation layer 122 is 1%-50%.

[0035] Optionally, the thickness of the polyanion layer 121 and the polycation layer 122 are independently selected from 0.1 μm-10 μm, and more preferably 0.5 μm-5 μm, which can better debond during transfer and form a thinner polycation layer 122 on the solid electrolyte layer 13 .

[0036] Optionally, the solid electrolyte layer 13 is selected from a sulfide solid electrolyte layer, a halide solid electrolyte layer, etc., and transfer printing can be achieved. Among them, the sulfide solid electrolyte used in the sulfide solid electrolyte layer is selected from at least one of LGPS, LSPS, LPS, and Li6PS5X, and X is selected from at least one of Cl, Br or I. When the present invention uses a sulfide solid electrolyte, a weakly polar or non-polar binder can be selected, such as polyvinylidene fluoride, vinylidene fluoride hexafluoropropylene copolymer, polytetrafluoroethylene, polyimide, ethylene propylene rubber, butyl rubber, fluororubber, styrene-butadiene rubber, nitrile rubber, hydrogenated nitrile rubber, hydrogenated styrene-butadiene-styrene copolymer, styrene-butadiene-styrene copolymer and other styrene thermoplastic elastomers, which can ensure the chemical stability of the sulfide solid electrolyte, wherein the mass fraction of the binder in the sulfide solid electrolyte layer is preferably 1%-10%.

[0037] Optionally, the solid electrolyte layer 13 has a thickness of 10 μm-100 μm.

[0038] Optionally, the electrode sheet 2 can be a positive electrode sheet or a negative electrode sheet, both of which include a current collector and an active material coating coated on the surface of the current collector. The present invention preferably uses a negative electrode sheet, transfers the solid electrolyte layer 13 and the polycation layer 122 to the active material coating of the negative electrode sheet, and then cooperates with the positive electrode sheet to construct an all-solid-state battery, the effect is better.

[0039] Optionally, when a voltage is applied between the transfer component and the electrode sheet, the voltage intensity is 0.1V-5V, more preferably 0.5V-1.5V, and the current direction is from the transfer component to the electrode sheet, which can not only enable the polyanion layer 121 and the polycation layer 122 to quickly debond and realize transfer, but also ensure the stability of the solid electrolyte layer 13.

[0040] Continue to see Figure 2 The present invention also provides an electrode sheet composite prepared by the preparation method, comprising an electrode sheet 2 and a solid electrolyte layer 13 and a polycation layer 122 sequentially stacked on the active material coating of the electrode sheet 2.

[0041] Among them, the electrode sheet 2 can be a positive electrode sheet or a negative electrode sheet. When the electrode sheet 2 is a positive electrode sheet, the electrode sheet complex includes a positive electrode sheet and a solid electrolyte layer 13 and a polycation layer 122 stacked in sequence on the active material coating of the positive electrode sheet. When the electrode sheet 2 is a negative electrode sheet, the electrode sheet complex includes a negative electrode sheet and a solid electrolyte layer 13 and a polycation layer 122 stacked in sequence on the active material coating of the negative electrode sheet.

[0042] The present invention also provides an all-solid-state battery, including the electrode sheet composite. Specifically, when the electrode sheet 2 is a positive electrode sheet, the electrode sheet composite and the negative electrode sheet cooperate to construct the all-solid-state battery, and the polycation layer 122 in the electrode sheet composite faces the negative electrode sheet; when the electrode sheet 2 is a negative electrode sheet, the electrode sheet composite and the positive electrode sheet cooperate to construct the all-solid-state battery, and the polycation layer 122 in the electrode sheet composite faces the positive electrode sheet.

[0043] The present invention also provides an electrical device, wherein the electrical device uses the all-solid-state battery.

[0044] Hereinafter, the electrode sheet composite and its preparation method, all-solid-state battery and its application will be further described through the following specific examples.

[0045] Example 1

[0046] According to molar parts, 40 parts of the copolymer of 3-sulfopropyl lithium acrylate and 1-ethyl-3-methyl imidazolium chloride were mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile, and then coated on aluminum foil and dried to obtain a polyanion layer with a thickness of 1 μm; according to molar parts, 40 parts of the copolymer of 2-bromoethyl acrylate and 1-butyl imidazolium were mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile, and then coated on the polyanion layer and dried to obtain a polycation layer with a thickness of 1 μm. 99 parts of sulfide LPSCl were mixed with 1 part of hydrogenated nitrile rubber binder to prepare a sulfide solid electrolyte layer with a thickness of 60 μm on the surface of the polycation layer to obtain a transfer component.

[0047] The negative electrode sheet and the prepared transfer component are laminated and placed between two rollers, and the distance between the two rollers is adjusted so that the sulfide solid electrolyte layer contacts the active coating of the negative electrode sheet. Then, a forward bias voltage of 1.0V is applied to the aluminum foil of the transfer component and the current collector of the electrode sheet to transfer the sulfide solid electrolyte layer to the active coating surface of the negative electrode sheet.

[0048] Example 2

[0049] According to molar parts, 40 parts of the copolymer of 3-sulfopropyl lithium acrylate and 1-ethyl-3-methyl imidazolium chloride were mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile, and then coated on aluminum foil and dried to obtain a polyanion layer with a thickness of 1 μm; according to molar parts, 40 parts of the copolymer of 2-bromoethyl acrylate and 1-butyl imidazolium were mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile, and then coated on the polyanion layer and dried to obtain a polycation layer with a thickness of 1 μm. 99 parts of sulfide LPSCl were mixed with 1 part of hydrogenated nitrile rubber binder to prepare a sulfide solid electrolyte layer with a thickness of 60 μm on the surface of the polycation layer to obtain a transfer component.

[0050] The negative electrode sheet and the prepared transfer component are laminated and placed between two rollers, and the distance between the two rollers is adjusted so that the sulfide solid electrolyte layer contacts the active coating of the negative electrode sheet. Then, a forward bias voltage of 3.0V is applied to the aluminum foil of the transfer component and the current collector of the electrode sheet to transfer the sulfide solid electrolyte layer to the surface of the active coating of the negative electrode sheet.

[0051] Example 3

[0052] The only difference between Example 3 and Example 2 is that the sulfide solid electrolyte layer is made by mixing 95 parts of sulfide LPSCl and 5 parts of hydrogenated nitrile rubber binder.

[0053] Example 4

[0054] According to molar parts, 40 parts of the copolymer of 3-sulfopropyl lithium acrylate and 1-ethyl-3-methyl imidazolium chloride were mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile, and then coated on aluminum foil and dried to obtain a polyanion layer with a thickness of 1 μm; according to molar parts, 40 parts of the copolymer of 2-bromoethyl acrylate and 1-butyl imidazolium were mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile, and then coated on the polyanion layer and dried to obtain a polycation layer with a thickness of 1 μm. 99 parts of sulfide LPSCl were mixed with 1 part of hydrogenated nitrile rubber binder to prepare a sulfide solid electrolyte layer with a thickness of 60 μm on the surface of the polycation layer to obtain a transfer component.

[0055] The negative electrode sheet and the prepared transfer component are laminated and placed between two rollers, and the distance between the two rollers is adjusted so that the sulfide solid electrolyte layer contacts the active coating of the negative electrode sheet. Then, a forward bias voltage of 5.0V is applied to the aluminum foil of the transfer component and the current collector of the electrode sheet to transfer the sulfide solid electrolyte layer to the surface of the active coating of the negative electrode sheet.

[0056] Example 5

[0057] According to molar parts, 40 parts of the copolymer of 3-sulfopropyl lithium acrylate and 1-ethyl-3-methyl imidazolium chloride were mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile, and then coated on aluminum foil and dried to obtain a polyanion layer with a thickness of 0.5 μm; according to molar parts, 40 parts of the copolymer of 2-bromoethyl acrylate and 1-butyl imidazolium were mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile, and then coated on the polyanion layer and dried to obtain a polycation layer with a thickness of 0.5 μm. 99 parts of sulfide LPSCl were mixed with 1 part of hydrogenated nitrile rubber binder to prepare a sulfide solid electrolyte layer with a thickness of 60 μm on the surface of the polycation layer to obtain a transfer component.

[0058] The negative electrode sheet and the prepared transfer component are laminated and placed between two rollers, and the distance between the two rollers is adjusted so that the sulfide solid electrolyte layer contacts the active coating of the negative electrode sheet. Then, a forward bias voltage of 1.0V is applied to the aluminum foil of the transfer component and the current collector of the electrode sheet to transfer the sulfide solid electrolyte layer to the active coating surface of the negative electrode sheet.

[0059] Example 6

[0060] According to molar parts, 40 parts of the copolymer of 3-sulfopropyl lithium acrylate and 1-ethyl-3-methyl imidazolium chloride were mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile, and then coated on aluminum foil and dried to obtain a polyanion layer with a thickness of 3 μm; according to molar parts, 40 parts of the copolymer of 2-bromoethyl acrylate and 1-butyl imidazolium were mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile, and then coated on the polyanion layer and dried to obtain a polycation layer with a thickness of 3 μm. 99 parts of sulfide LPSCl were mixed with 1 part of hydrogenated nitrile rubber binder to prepare a sulfide solid electrolyte layer with a thickness of 60 μm on the surface of the polycation layer to obtain a transfer component.

[0061] The negative electrode sheet and the prepared transfer component are laminated and placed between two rollers, and the distance between the two rollers is adjusted so that the sulfide solid electrolyte layer contacts the active coating of the negative electrode sheet. Then, a forward bias voltage of 1.0V is applied to the aluminum foil of the transfer component and the current collector of the electrode sheet to transfer the sulfide solid electrolyte layer to the active coating surface of the negative electrode sheet.

[0062] Example 7

[0063] The only difference between Example 7 and Example 6 is that the sulfide solid electrolyte layer is made by mixing 95 parts of sulfide LPSCl and 5 parts of hydrogenated nitrile rubber binder.

[0064] Example 8

[0065] According to molar parts, 40 parts of the copolymer of 3-sulfopropyl lithium acrylate and 1-ethyl-3-methyl imidazolium chloride were mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile, and then coated on aluminum foil and dried to obtain a polyanion layer with a thickness of 1 μm; according to molar parts, 40 parts of the copolymer of 2-bromoethyl acrylate and 1-butyl imidazolium were mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile, and then coated on the polyanion layer and dried to obtain a polycation layer with a thickness of 1 μm. 99 parts of sulfide LPSCl were mixed with 1 part of hydrogenated nitrile rubber binder to prepare a sulfide solid electrolyte layer with a thickness of 30 μm on the surface of the polycation layer to obtain a transfer component.

[0066] The negative electrode sheet and the prepared transfer component are laminated and placed between two rollers, and the distance between the two rollers is adjusted so that the sulfide solid electrolyte layer contacts the active coating of the negative electrode sheet. Then, a forward bias voltage of 1.0V is applied to the aluminum foil of the transfer component and the current collector of the electrode sheet to transfer the sulfide solid electrolyte layer to the active coating surface of the negative electrode sheet.

[0067] Example 9

[0068] According to molar parts, 40 parts of the copolymer of 3-sulfopropyl lithium acrylate and 1-ethyl-3-methyl imidazolium chloride were mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile, and then coated on aluminum foil and dried to obtain a polyanion layer with a thickness of 1 μm; according to molar parts, 40 parts of the copolymer of 2-bromoethyl acrylate and 1-butyl imidazolium were mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile, and then coated on the polyanion layer and dried to obtain a polycation layer with a thickness of 1 μm. 99 parts of sulfide LPSCl were mixed with 1 part of hydrogenated nitrile rubber binder to prepare a sulfide solid electrolyte layer with a thickness of 90 μm on the surface of the polycation layer to obtain a transfer component.

[0069] The negative electrode sheet and the prepared transfer component are laminated and placed between two rollers, and the distance between the two rollers is adjusted so that the sulfide solid electrolyte layer contacts the active coating of the negative electrode sheet. Then, a forward bias voltage of 1.0V is applied to the aluminum foil of the transfer component and the current collector of the electrode sheet to transfer the sulfide solid electrolyte layer to the active coating surface of the negative electrode sheet.

[0070] Example 10

[0071] The only difference between Example 10 and Example 2 is that the sulfide solid electrolyte layer is made by mixing 95 parts of sulfide LPSCl and 5 parts of hydrogenated nitrile rubber binder.

[0072] Embodiment 11

[0073] According to molar proportion, 40 parts of the copolymer of 3-sulfopropyl acrylate lithium and 1-ethyl-3-methylimidazolium chloride were mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile for reaction, and then coated on aluminum foil and dried to obtain a polyanion layer with a thickness of 1 μm; according to molar proportion, 40 parts of 1-(6-(acryloyloxy)-hexyl)-3-ethylimidazolium-bis(trifluoromethylsulfonyl)imide were mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile for reaction, and then coated on the polyanion layer and dried to obtain a polycation layer with a thickness of 1 μm. 99 parts of sulfide LPSCl were mixed with 1 part of hydrogenated nitrile rubber binder to prepare a sulfide solid electrolyte layer with a thickness of 60 μm on the surface of the polycation layer to obtain a transfer component.

[0074] Example 12

[0075] According to molar parts, the copolymer of polystyrene benzyltrimethylammonium chloride and hydrogenated polybutadiene is mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile for reaction, then coated on aluminum foil and dried to obtain a polyanion layer with a thickness of 1 μm; according to molar parts, 40 parts of the copolymer of 2-bromoethyl acrylate and 1-butylimidazolium are mixed with 8 parts of polyethylene glycol diacrylate and 0.2 parts of azobisisobutyronitrile for reaction, then coated on the polyanion layer and dried to obtain a polycation layer with a thickness of 1 μm. 99 parts of sulfide LPSCl are mixed with 1 part of hydrogenated nitrile rubber binder to prepare a sulfide solid electrolyte layer with a thickness of 60 μm on the surface of the polycation layer to obtain a transfer component.

[0076] Comparative Example 1

[0077] The only difference between Comparative Example 1 and Example 1 is that the sulfide solid electrolyte layer is prepared by directly coating on the aluminum foil without an interface layer.

[0078] Comparative Example 2

[0079] The only difference between Comparative Example 2 and Example 1 is that no voltage is applied to the aluminum foil of the transfer component and the current collector of the electrode sheet.

[0080] The area of ​​the sulfide solid electrolyte layer transferred to the negative electrode sheet in the above embodiments and comparative examples was counted, and the transfer efficiency was calculated. The statistical method was: referring to the hundred-grid adhesion test standard, the percentage of the area of ​​the sulfide solid electrolyte layer transferred to the negative electrode sheet to the area of ​​the sulfide solid electrolyte layer in the transfer component before transfer was counted. The test results are shown in Table 1 below.

[0081] Table 1

[0082] Transfer efficiency Example 1 100% Example 2 98% Example 3 100% Example 4 97% Example 5 99% Example 6 96% Example 7 100% Example 8 99% Example 9 94% Example 10 100% Embodiment 11 100% Example 12 100% Comparative Example 1 82% Comparative Example 2 75%

[0083] As can be seen from Table 1, the transfer efficiency of the sulfide solid electrolyte layer in the embodiment of the present invention is significantly higher than that in the comparative example, indicating that the transfer method of the present invention can effectively improve the transfer efficiency. In addition, the present invention can achieve a complete transfer effect on the basis of a low amount of binder, ensuring the stability of the sulfide solid electrolyte, and can also achieve a complete transfer effect by adjusting the binder, the thickness of the interface layer, the voltage intensity and other conditions.

[0084] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0085] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing an electrode sheet composite, characterized in that: The following steps are involved: An interface layer and a solid electrolyte layer are sequentially prepared on any surface of a conductive substrate to obtain a transfer component, wherein the interface layer comprises a polyanion layer and a polycation layer sequentially stacked on the conductive substrate; An electrode sheet is provided, and the electrode sheet is laminated to the transfer component so that the solid electrolyte layer of the transfer component contacts the active material coating of the electrode sheet. Then, a voltage is applied between the transfer component and the electrode sheet so that the solid electrolyte layer and the polycationic layer in the transfer component are transferred to the surface of the active material coating of the electrode sheet, thereby obtaining an electrode sheet complex.

2. The method for preparing an electrode sheet composite according to claim 1, characterized in that: The anionic polymer used in the polyanionic layer is selected from at least one of a copolymer of 3-sulfopropyl acrylate lithium and 1-ethyl-3-methylimidazolium chloride, and a copolymer of polystyrene benzyltrimethylammonium chloride and hydrogenated polybutadiene; And / or, the cationic polymer used in the polycationic layer is at least one selected from a copolymer of 2-bromoethyl acrylate and 1-butylimidazolium, and 1-(6-(acryloyloxy)-hexyl)-3-ethylimidazolium-bis(trifluoromethylsulfonyl)imide.

3. The method for preparing an electrode sheet composite according to claim 1, characterized in that: The polycation layer also includes lithium salt.

4. The method for preparing an electrode sheet composite according to claim 1, characterized in that: The thickness of the polyanion layer and the polycation layer are independently selected from 0.1 μm to 10 μm.

5. The method for preparing an electrode sheet composite according to claim 1, characterized in that: When a voltage is applied between the transfer component and the electrode sheet, the voltage intensity is 0.1V-5V, and the current direction is from the transfer component to the electrode sheet.

6. The method for preparing an electrode sheet composite according to claim 1, characterized in that: The solid electrolyte layer is selected from a sulfide solid electrolyte layer; And / or, the thickness of the solid electrolyte layer is 10 μm-100 μm.

7. The method for preparing an electrode sheet composite according to claim 1, characterized in that: The electrode sheet is selected from a positive electrode sheet or a negative electrode sheet.

8. An electrode sheet composite, characterized in that: The electrode sheet composite is prepared by the preparation method of any one of claims 1 to 7, comprising an electrode sheet and a solid electrolyte layer and a polycation layer sequentially stacked on the active material coating of the electrode sheet.

9. An all-solid-state battery, characterized in that: Comprising the electrode sheet composite as claimed in claim 8.

10. An electrical device, characterized in that: The electrical equipment uses the all-solid-state battery as claimed in claim 9.

Citation Information

Cited By

  • Battery cell complex, preparation method thereof and all-solid-state battery

    CN121688149A

  • Cell composites and their preparation methods and all-solid-state batteries

    CN121688149B